2007
DOI: 10.1002/ange.200604265
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Simultaneous Multianalyte Detection of DNA by Dual‐Wavelength Surface‐Enhanced Resonance Raman Scattering

Abstract: SERRS gut: Die quantitative Detektion von fünf markierten Oligonucleotiden gelingt durch das im Titel genannte Verfahren SERRS, ohne dass eine Trennung erforderlich ist. Die Empfindlichkeit der Mehrfachanalyse ist dabei die gleiche wie beim Nachweis der einzelnen Farbstoffe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 14 publications
0
46
0
1
Order By: Relevance
“…Consequently several SERRS-labeled oligonucleotides can be simultaneously detected if the absorption maxima of the tags are close enough to the laser excitation wavelength [25][26][27][28][29][30]. Maximum absorption of HEX and R6G is at 535 and 524 nm, respectively, and can therefore be simultaneously measured with an argon laser tuned at 514.5 nm [27,29,31,37]. Moreover, their Raman signals enable specific discrimination of each probe, because of its most intense peaks centered at 1632 cm −1 and 1650 cm −1 for HEX and R6G, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently several SERRS-labeled oligonucleotides can be simultaneously detected if the absorption maxima of the tags are close enough to the laser excitation wavelength [25][26][27][28][29][30]. Maximum absorption of HEX and R6G is at 535 and 524 nm, respectively, and can therefore be simultaneously measured with an argon laser tuned at 514.5 nm [27,29,31,37]. Moreover, their Raman signals enable specific discrimination of each probe, because of its most intense peaks centered at 1632 cm −1 and 1650 cm −1 for HEX and R6G, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several SERRS-labeled oligonucleotides can be simultaneously detected [25][26][27][28][29][30]. A variety of molecules can be detected by SERRS if their absorption maxima are close enough to the laser excitation wavelength.…”
Section: Serrs-labelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2001 and 2003, the first examples of a SERRS DNA 2-plex, using rhodamine-and HEX-labelled oligonucleotides [48], and a 3-plex, using FAM, TET and Cy3, were developed by Graham and co-workers [49]. Faulds et al demonstrated the first 5-plex system where FAM-, Cy5.5-, BODIPY-, R6G-and ROX-labelled oligonucleotides were detected in situ as shown in Figure 11.5 [50]. In the study, the oligonucleotide mixture was maintained at a concentration of 1.82 × 10 −9 mol dm −3 throughout.…”
Section: Multiplexingmentioning
confidence: 99%
“…It has been recognized that the SERRS cross sections for common fluorophores are similar to fluorescence and has the additional advantages of possessing much higher information content: the spectrum contains many characteristic vibrational peaks [31]. These possible advantages for SERRS have been identified, and the exploration of the potential of SERRS for multiplexing applications is an active area of research [32,33].…”
Section: Lb Sm-serrs To Biologically Relevant Systemsmentioning
confidence: 99%